0317 Interaction of Sleep and Emotion Across the Menstrual Cycle. (25th May 2022) - Meers, Jessica; Bower, Joanne; Nowakowski, Sara; Alfano, Candice
Abstract: Introduction: Women experience increased risk for sleep and affective disorders compared to men, attributed in part to monthly oscillations in sex hormones. Emotional functioning worsens during the perimenstrual phase. There is increasing evidence that sleep continuity also decreases during this phase. Thus, this study examined the interactive effects of sleep and menstrual phase on emotion across two menstrual cycles in healthy women. Methods: Participants (N=51, 43% Caucasian) aged 18-35 (m=23.67) completed actigraphy and daily sleep/emotion diaries over two menstrual cycles (m days=51.29). Cycles were identified via date of menses and urinary ovulation detection, and coded into four phases: perimenstrual, mid-follicular, periovulatory, and mid-luteal. The perimenstrual phase was defined the 3 days prior to and the 3 days following menses onset. Variables included diary and actigraphic total wake time (TWT), daily ratings of positive (happy, calm, enthusiastic) and negative (angry, afraid, sad) affect using a 9-point scale. Relationships between phase, sleep, and emotion were estimated using multistep hierarchical linear modeling. Pandemic-related stress and daily US and region-specific COVID-19 case counts were included as covariates in adjusted models. Results: Mean menstrual cycle length was 28.61±2.69 days. Menstrual phase was first entered into models as predictors for sleep and emotion variables independently. The perimenstrual phase positively predicted anger (p<.001) but no other emotions. Additionally, the perimenstrual phase predicted higher rates of TWT, such that diary-reported TWT was 8-16 minutes longer during the perimenstrual (m=67.54, SE=3.37) compared to other phases (p<.001). Actigraphic TWT was also increased by 4-7 minutes (m=61.54, SE=3.37) in the perimenstrual phase (p<.001). A second model included the interaction term, TWT*phase to the original model. Positive emotions were .05-.10 points lower (p's=.006-.02) when TWT was greater in the perimenstrual phase. Conclusion: Menstruating women experienced greater rates of anger and sleep disruption during the perimenstrual phase compared to other phases. When poor sleep occurred during the perimenstrual phase, however, women reported reduced positive emotions. Sleep disruptions, particularly occurring during the perimenstrual phase, may be an important intervention target for women at risk for affective disorders. Future studies should be mindful to assess menstrual phases when assessing sleep and circadian rhythm. Support (If Any):